2001
DOI: 10.1016/s0960-9822(01)00160-9
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprints of anergic T cells

Abstract: Peripheral T cell tolerance may result from activation-induced cell death [1], anergy [1], and/or immune response modulation by regulatory T cells [2]. In mice that express a transgenic receptor specific for peptide 111-119 of influenza hemagglutinin presented by E(d) class II MHC molecules as well as hemagglutinin under control of the immunoglobulin-kappa promoter, we have found that anergic T cells [3] can also have immunoregulatory function and secrete IL-10 [4]. In order to obtain information on molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
82
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 20 publications
3
82
0
3
Order By: Relevance
“…This provides direct evidence for PD-1 as a negative regulator of immune responses in vivo [13]. PD-1 mRNA is expressed at high levels in CD4 + CD25 + regulatory T cells (Treg) and anergic T cells [14,15], suggesting the possible involvement of PD-1 in regulating Treg function and T cell tolerance.…”
Section: Introductionmentioning
confidence: 70%
“…This provides direct evidence for PD-1 as a negative regulator of immune responses in vivo [13]. PD-1 mRNA is expressed at high levels in CD4 + CD25 + regulatory T cells (Treg) and anergic T cells [14,15], suggesting the possible involvement of PD-1 in regulating Treg function and T cell tolerance.…”
Section: Introductionmentioning
confidence: 70%
“…Studies on anergenic T cells have uncovered a complex mechanism involving a number of negative regulators [33] including EGR2, EGR3 and the E3-ubiquitin ligases, GRAIL, ITCH, and CblB [34]. Both EGR2 and EGR3 are involved in the induction and maintenance of T-cell anergy [35].…”
Section: Discussionmentioning
confidence: 99%
“…In our studies, IFN-γ production is not observed when splenocytes from infected or injected mice are stimulated with FhTeg and in the case of infection even after the addition of IL-2. Similarly, FhTeg restimulated cells do not exhibit other characteristics associated with exhausted T cells such as high deletion of cells and apoptosis, which further supports its role in the induction of anergy.Studies on anergenic T cells have uncovered a complex mechanism involving a number of negative regulators [33] including EGR2, EGR3 and the E3-ubiquitin ligases, GRAIL, ITCH, and CblB [34]. Both EGR2 and EGR3 are involved in the induction and maintenance of T-cell anergy [35].…”
mentioning
confidence: 99%
“…Up-regulation of PD-L1 during Th1-driven inflammation might serve as a negative feedback mechanism for controlling responses in the target organ and limit pathogenic T cell responses in the brain. Furthermore, PD-1 mRNA is highly expressed in CD4 ϩ CD25 ϩ T regulatory cells (Treg) which have been shown to regulate EAE (24,25). Thus, the increased MOG-specific CD4 ϩ T cell responses in PD-L1 Ϫ/Ϫ mice might reflect multiple negative regulatory functions for PD-L1: (i) limiting expansion and͞or Th1 differentiation of naïve CD4 ϩ T cells, (ii) negatively regulating reactivation of MOG-specific effector CD4 ϩ T cells in the target organ, and (iii) limiting expansion of antigen-specific T cells through engagement of PD-1 on Tregs.…”
Section: Discussionmentioning
confidence: 99%